Correction: Ionic-caged heterometallic bismuth–platinum complex exhibiting electrocatalytic CO2 reduction. Issue 14 (20th March 2020) - Yoshida, Takefumi; Md. Ahsan, Habib; Zhang, Hai-Tao; Izuogu, David Chukwuma; Abe, Hitoshi; Ohtsu, Hiroyoshi; Yamaguchi, Tadashi; Breedlove, Brian K.; Thom, Alex J. W.; Yamashita, Masahiro
Abstract : Correction for 'Ionic-caged heterometallic bismuth–platinum complex exhibiting electrocatalytic CO2 reduction' by Takefumi Yoshida et al., Dalton Trans., 2020, 49, 2652–2660.